Comparison of long-term results of carotid endarterectomy for asymptomatic carotid artery stenosis - Demirel, S. (Gefasschirurgie, 2018)
This article summarizes the current study situation on treatment of asymptomatic carotid artery stenosis and discusses the evidence situation in the literature. The 10-year results of the ACST study have shown that in comparison to conservative treatment, carotid endarterectomy (CEA) has retained a positive long-term effect on the reduction of all forms of stroke. All multicenter randomized controlled trials comparing CEA with carotid artery stenting (CAS) and, in particular the SAPHIRE and CAVATAS studies, have in common that despite a basic evidence level of Ib, the case numbers of asymptomatic patients are too small for a conclusive therapy recommendation. In the overall assessment of the CREST study the resulting difference in the questionable endpoint of “perioperative myocardial infarction” in favor of the CAS methods, could not be confirmed for exclusively asymptomatic patients. In the long-term course of the CREST study, both methods were classified as equivalent, even when the 4‑year results of periprocedural and postprocedural stroke rates in the separate assessment of the asymptomatic study participants clearly favored the CEA. The results of the ACST-1 study showed an equivalent effect of both treatment methods with respect to all investigated endpoints; however, the unequal sizes of the groups in addition to the statistically insufficient case numbers put a question mark on the validity of the study results. The results of the ASCT-2 and CREST-2 studies are to be awaited, which also investigate the significance of “CEA versus CAS” (ASCT-2) and “CEA/CAS + best medical treatment (BMT) versus BMT alone” in only asymptomatic stenoses. The current S3 guidelines allow operative therapy to be considered in patients with a 60–99% asymptomatic carotid artery stenosis, because the risk of stroke is statistically significantly reduced.